Strengthening the Role of Artificial Intelligence Technology in the Role of Court Judges in Indonesia - Yanwiyatono Yanwiyatono; Herman Bakir (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
This research explores the strengthening role of artificial intelligence (AI) technology in supporting the duties and responsibilities of court judges in Indonesia. In the digital era, the integration of AI in the judicial system is necessary to improve efficiency, accuracy, and fairness in legal decision-making. This research uses a qualitative method with literature studies, in-depth interviews, and case analysis from other countries that have implemented AI in their justice systems. The results show that AI can reduce judges' workload, speed up case resolution, and minimize human error and bias. However, there are challenges such as ethical issues, data privacy, and public trust in AI decisions. This research emphasizes the need for a clear regulatory framework and specialized training for judges to ensure the effective and responsible use of AI. In addition, the importance of collaboration between governments, legal institutions, and technology developers to create AI solutions that comply with the principles of fairness and transparency was expressed. In conclusion, although AI has great potential to strengthen the role of judges in Indonesia, its implementation must be done carefully to maintain the principles of fairness.